Heat transfer in packed-beds of agricultural waste with low rates of air flow applicable to solid-state fermentation - Casciatori, Fernanda Perpétua; Thoméo, João Cláudio [UNESP] (Elsevier, 2018)
Heat transfer studies were carried out in packed-beds (PBs) heated by the wall and percolated by low air flow rates. Porous media were composed by particles of sugarcane bagasse (SCB) and by a mixture of particles of SCB, orange pulp and peel (OPP) and wheat bran (WB) at proportion SCB:OPP:WB 1:2:2 w/w (composed medium), agricultural waste used as substrates in bioreactors of solid-state fermentation (SSF), an interesting biotechnological application of PBs. Once metabolic heat generated has to be dissipated, heat transfer studies and thermal parameters are required. Tube-to-particle diameter ratio was D/dp = 260, bed height ranged from L = 60 to 180 mm, while air flow rate ranged from 400 to 1200 L/h. Air temperature was 40 °C and wall temperature 65 °C. The outlet bed temperatures (TL) were measured by ring-shaped sensors and by aligned thermocouples. Average temperatures (Tavg) and global heat transfer coefficients (U) were calculated separately for central region of the beds and for wall-vicinity. Radial effective thermal conductivity (Λr) and wall-to-fluid convective heat transfer coefficient (αwall) have been estimated by means of the traditional two-parameters model. Radial temperature profiles at bed outlet were flattened in the central region and convergent at the edge of the packs. The two-regions approximation for U calculations showed to be appropriate for both packs. Global coefficient U, thermal conductivity Λr and convective coefficient αwall increased with increasing air flow rate and decreased with bed height. Λr tended to the stagnant value of the thermal conductivity and αwall were lower than 50 W/m2/°C, addressing the difficulty on removing metabolic heat from PBs of SSF.
Keywords: Bioreactors; Heat transfer; Packed-beds; Solid waste; Solid-state fermentation